Kinetic Spectrophotometric Determination of Vitamin C in Fruit Juices via Oxidation Reaction with Dichlorophenolindophenol (DCPIP) - Shihad, Arshed AbdAli (American Journal of Biology and Natural Sciences, 2026)
A validated kinetic spectrophotometric method was developed for the determination of vitamin C (ascorbic acid) in fruit juice samples using 2,6-dichlorophenolindophenol (DCPIP) as an oxidizing agent. The method is based on monitoring the decrease in absorbance of DCPIP at 520 nm, following a pseudo-first-order kinetic behavior in the presence of excess reagent. Calibration curves constructed from standard ascorbic acid solutions exhibited excellent linearity (R² = 0.997) within the range of 10–100 mg/L. Method validation confirmed high sensitivity (LOD: 2.5 mg/L; LOQ: 8.0 mg/L), accuracy (recoveries 97.5–102.3%), and precision (RSD ≤ 3%). The procedure was successfully applied to commercial fruit juices, where vitamin C content varied among samples, with lemon and orange juices showing the highest concentrations and apple juice the lowest. The results are consistent with reported nutritional profiles, confirming the method’s reliability. Owing to its simplicity, cost-effectiveness, and reproducibility, the proposed approach offers a practical alternative for routine analysis of vitamin C in food and beverage quality control.